2014
DOI: 10.1007/s11356-014-3536-x
|View full text |Cite
|
Sign up to set email alerts
|

Selective recovery of dissolved Fe, Al, Cu, and Zn in acid mine drainage based on modeling to predict precipitation pH

Abstract: Mining activities have caused serious environmental problems including acid mine drainage (AMD), the dispersion of mine tailings and dust, and extensive mine waste. In particular, AMD contaminates soil and water downstream of mines and generally contains mainly valuable metals such as Cu, Zn, and Ni as well as Fe and Al. In this study, we investigated the selective recovery of Fe, Al, Cu, Zn, and Ni from AMD. First, the speciation of Fe, Al, Cu, Zn, and Ni as a function of the equilibrium solution pH was simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…Metals 2019, 9, x FOR PEER REVIEW values of calculated Saturation Indices (SI). In the case o lead, and manganese, these SI-values were negative wit Park et al [36] concluded that in synthetic multim amorphous ferric oxyhydroxide and then was transfo internal atomic rearrangement to hematite. These two t other, and one of them is dominant depending on the re…”
Section: α−Tfeo(oh)mentioning
confidence: 97%
See 4 more Smart Citations
“…Metals 2019, 9, x FOR PEER REVIEW values of calculated Saturation Indices (SI). In the case o lead, and manganese, these SI-values were negative wit Park et al [36] concluded that in synthetic multim amorphous ferric oxyhydroxide and then was transfo internal atomic rearrangement to hematite. These two t other, and one of them is dominant depending on the re…”
Section: α−Tfeo(oh)mentioning
confidence: 97%
“…Software simulation did not predict nickel precipitated during the neutralization test. Park et al [36] found that in the quaternary solution, Ni completely precipitated at pH 8.4. Precipitation of nickel started at pH 7, and the pH required for complete precipitation of Ni was not reached in this experiment.…”
Section: Oxidation Precipitation Dehydrationmentioning
confidence: 99%
See 3 more Smart Citations